1998
DOI: 10.1128/iai.66.12.6058-6062.1998
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli and Streptococci Induce Interleukin-12 (IL-12), IL-18, and Gamma Interferon Production in Human Peripheral Blood Mononuclear Cells

Abstract: Human peripheral blood mononuclear cells (PBMC) were stimulated with three nonpathogenic Lactobacillus strains and with one pathogenic Streptococcus pyogenes strain, and cytokine gene expression and protein production were analyzed. All bacteria strongly induced interleukin-1β (IL-1β), IL-6, and tumor necrosis factor alpha mRNA expression and protein production. S. pyogenes was the most potent inducer of secretion of IL-12 and gamma interferon (IFN-γ), and two of three Lactobacillusstrains induced IL-12 and IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
112
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(128 citation statements)
references
References 40 publications
12
112
0
4
Order By: Relevance
“…All Lactobacillus strains tested in our study stimulated IL-10, IFN-g and TNF-a production both after 1 and 4 days of culture as well as IL-1b after 1 day of culture. In support of our results, Lactobacillus strains are generally strong inducers of the proinflammatory cytokines TNF-a (Miettinen et al, 1998;Maragkoudakis et al, 2006;Timmerman et al, 2007) and IL-12 (Miettinen et al, 1998;Hessle et al, 1999;Haller et al, 2000;Shida et al, 2006), although several studies observed that specific lactic acid bacteria yield a low or nonsignificant increase in IL-12 production by hPBMC (Niers et al, 2005;Drouault-Holowacz et al, 2006). In our study, all L. plantarum strains tested stimulated IL-12 production, while most L. acidophilus strains failed to do so, which confirms that the difference in IL-12 induction observed in the reported studies is caused by the use of different species and strains.…”
Section: Discussionsupporting
confidence: 89%
“…All Lactobacillus strains tested in our study stimulated IL-10, IFN-g and TNF-a production both after 1 and 4 days of culture as well as IL-1b after 1 day of culture. In support of our results, Lactobacillus strains are generally strong inducers of the proinflammatory cytokines TNF-a (Miettinen et al, 1998;Maragkoudakis et al, 2006;Timmerman et al, 2007) and IL-12 (Miettinen et al, 1998;Hessle et al, 1999;Haller et al, 2000;Shida et al, 2006), although several studies observed that specific lactic acid bacteria yield a low or nonsignificant increase in IL-12 production by hPBMC (Niers et al, 2005;Drouault-Holowacz et al, 2006). In our study, all L. plantarum strains tested stimulated IL-12 production, while most L. acidophilus strains failed to do so, which confirms that the difference in IL-12 induction observed in the reported studies is caused by the use of different species and strains.…”
Section: Discussionsupporting
confidence: 89%
“…It is however evident from the obtained results that probably more than one mechanism may be involved in the observed antiviral effect, as previously hypothesized in similar studies (Botić et al, 2007;Ivec et al, 2007). In addition, apart from ROS and attachment, the release of pro-inflammatory cytokines as interleukins (IL) 6 and 12 or the antiviral interferon-γ (IFN-γ), is an important mechanism by which probiotic bacteria may protect host cells (Miettinen et al, 1998;Hessle et al, 1999;Maassen et al, 2000;Ivec et al, 2007). The mechanism of action of the antiviral effects reported in this study needs to be further investigated and so a more detailed, holistic approach would need to be adopted, focusing less on the screening of LAB strains against various cell lines and viruses, and more on in depth studies of the phenomenon.…”
Section: Discussionmentioning
confidence: 52%
“…We examined the mechanism by which L. plantarum induces TRAIL. Previous reports showed that TRAIL is expressed on immu- nocytes after stimulation with IFN-a [16], IFN-c [17], and that the administration of lactobacilli induced the release of IFN-c [18]. Therefore, we hypothesized that L. plantarum induces TRAIL expression through IFN-a and/or IFN-c. We examined the involvement of IFN-a and/or IFN-c in the expression of the TRAIL on the surface of PBMC ( Fig.…”
Section: Trail Induction By L Plantarum Partly Depends On the Producmentioning
confidence: 95%